(untitled) (Asian Journal of Plant Biology, 2021)
Physical or chemical procedures could efficiently remove contaminants including pesticides such as carbamates from high concentrations of toxicants. Bioremediation, on the other hand, is frequently a less expensive option in the long term when used at low concentrations. Isolation of multiple toxicants removing microorganisms is the goal of bioremediation. In this paper we report on the molybdenum reduction of the bacterium and its ability to grow on the carbamates carbofuran and carbaryl as carbon sources. Both the carbamates carbofuran and carbaryl cannot support molybdenum reduction when used as the sole carbon sources. Between pH 6.0 and 6.8 and between 30 and 34 oC, the bacterium is most efficient in converting molybdate to Mo-blue. For molybdate reduction, glucose was shown to be the strongest electron donor, with maltose and sucrose coming in second and third, respectively, and d-mannitol and d-adonitol coming in last. Phosphate concentrations of 2.5 to 7.5 mM and molybdate concentrations of 20 to 30 mM are also needed. Identical to that of a decreased phosphomolybdate, the Mo-blue produced by the new Mo-reducing bacteria has an absorption spectrum similar to prior Mo-reducing bacteria. Inhibition of molybdenum reduction was 73.3, 50.1, 50.1 and 20.7 percent, respectively, by mercury, copper, silver and lead at 2 ppm. The bacterium was tentatively identified as Serratia sp. strain Amr-4 after biochemical investigation. This bacterium’s ability to detoxify a variety of toxicants is highly sought after, making it a significant bioremediation agent.